Pelatihan Manajemen Keuangan Keluarga pada Kelompok Masyarakat Dasa Wisma, Desa Soya - Latuserimala, Gerald; Putuhena, Meivi Sali; Tomasoa, Theodora Florence (Jurnal Pengabdian Arumbai, 2024)
Financial management is important in meeting family needs. The Covid-19 pandemic has added to the difficulties with the phenomenon of panic buying and decreased income. Family financial management is divided into short, medium, and long term. Through planning, fund allocation, implementation, and evaluation, families can manage finances effectively and efficiently. Community service activities in Soya Village aim to improve understanding and skills in financial management. Challenges include difficulty in identifying financial conditions and accessing investment information. The solution is to provide practical knowledge that can be applied daily. In conclusion, this activity is a small step in improving family financial stability. Financial management training at the Dasa Wisma Group in Soya Village improves the community's financial understanding. They learn the importance of financial management, stages, investment schemes, and implementation of spending plans. Positive responses show the relevance and need for this training, which is expected to help improve financial literacy and well-being.